(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article is dedicated to the actual and complex issue of tolerance and aggression in the society. The main task of this theoretical research is to seek a solution to the following three main questions: how this or that type of behavior is acquired, what factors trigger such behavioral types, and what factors support tolerant and aggressive behavior. The purpose of the article is not to provide a complete overview of all opinions on the issue of aggression and tolerance ever described in academic literature but rather an attempt to reveal extreme (at times mutually exclusive) approaches revealed during the critical analysis of this issue. The authors analyze the nature, motives, and various forms of aggression and tolerance and conclude about their contradictory unity, i.e. interconnection and interdependence of the aggression and tolerance. Key words: tolerance, tolerant behavior, aggression, aggressive behavior, forms of aggression.